Peran Manajemen Pendidikan Dalam Meningkatkan Mutu Pendidikan Inkulsi Pada Anak Berkebutuhan Khusus SDN Sungai Miai 5, Banjarmasin - Arifina, Lutfi Azzah; Putri, Julianor Vatika; vchananda, Syalsyabila alisyia; Suriansyah, Ahmad; Cinantya, Celia (CV. ITTC INDONESIA, 2024)
This study aims to describe how planning, organizing, implementing and supervising in management can improve the quality of inclusive education for children with special needs at SDN Sungai Miai 5, Banjarmasin using a descriptive qualitative research method. The study was conducted at SDN Sungai Miai 5, Banjarmasin City, South Kalimantan. The subjects in this study were the Principal, homeroom teacher, and teacher accompanying children with special needs (GPK). The research instruments consisted of observation sheets, structured interviews and documentation. The data obtained through the analysis of the stages of data reduction, data presentation and drawing conclusions of verification. Validation of the data obtained was carried out by triangulation of reliable sources. The results of the study showed that the service management implemented so as to improve the quality of inclusive education in Sungai Miai 5, Banjarmasin consisted of several stages and had been implemented well and ran optimally